2014
DOI: 10.1080/1064119x.2014.954180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Strength Increase of Marine Clay under Staged Embankment Loading: A Case Study

Abstract: This article presents a case history of the performance of a full-scale test embankment constructed on a marine soft clay deposit improved by prefabricated vertical drains (PVDs) in the east of China. For analyzing the subsoil behavior, a 2D FEM model is established, in which the PVD-improved effect is considered by a simplified method of equivalent vertical hydraulic conductivity. The calculated results can predict the settlement behavior well, however, the FEM gives an underestimate for the value of excess p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Jongmans [33] suggested that an influence radius of 50 m should be considered during pile driving. There can also be an additional load from embankment construction during urbanization [34,35], and cyclic loading due to traffic can also lead to the deformation of strata. According to an investigation made by Ling et al [36], traffic loading at an intersection of the Shanghai outer ring road could result in a residual settlement of 50 mm.…”
Section: Additional Loadmentioning
confidence: 99%
“…Jongmans [33] suggested that an influence radius of 50 m should be considered during pile driving. There can also be an additional load from embankment construction during urbanization [34,35], and cyclic loading due to traffic can also lead to the deformation of strata. According to an investigation made by Ling et al [36], traffic loading at an intersection of the Shanghai outer ring road could result in a residual settlement of 50 mm.…”
Section: Additional Loadmentioning
confidence: 99%
“…Shen et al [4] reported on a field test located near the Huangpu River in the Pudong New Development Area, China. In this field test, the single fluid system was used for horizontal jet grouting, where the metro tunnel stating shaft was protected by the excavation (Wu et al, 2015c;2016;2017a, b) [19,47,48]. Figure 8 shows the geotechnical profile and soil properties for this case history.…”
Section: Methods Verificationmentioning
confidence: 99%
“…The piezometric level of this confined aquifer is close to the ground surface. Additionally, in the hilly region, the bedrock fissure water widely distributed across an area of 743.3 km 2 usually has a very high piezometric level [52][53][54][55][56][57]. It is worth noting that the well-developed river network combined with the high precipitation provides abundant water resources that may worsen the geological conditions during shield tunneling [58][59][60][61][62][63][64][65][66].…”
Section: Hydrogeology and Engineering Geology Of Guangzhoumentioning
confidence: 99%